CARBON DIOXIDE MEDIATED DISSOLUTION OF CA-FELDSPAR: IMPLICATIONS FOR SILICATE WEATHERING - Berg A.; Banwart S.A. (My University, 2000)
Experimental studies on the dissolution kinetics of anorthite under N2(g) and CO2(g) atmospheres at 25°C in electrolyte solutions, pH range 5.5<pH<8.5, have been performed using laboratory flow-through reactors. Aluminum release from anorthite is accelerated in the neutral to near-basic pH region. Because Al is the slowest dissolving network-forming cation under these conditions, we propose that accelerated Al release corresponds to a long-term acceleration of anorthite dissolution. The rate of Al release from anorthite correlates with solution concentration of carbonate ion according to a fractional-order empirical rate law; k=(1.1+/-1)x10-7 mol0.76 m-1.52 h-1:Rate=k[CO2-3]0.24We propose a two-step reaction mechanism where inorganic carbon is rapidly adsorbed, forming a reactive bi-dentate surface Al-carbonate complex that is released to solution in a much slower, irreversible step. The rate expression formally derived from this dissolution mechanism is consistent with the observed dependence of Al release rate on the master variables PCO2 and pH. A comparison with published data on the weathering kinetics of plagioclase in solutions of oxalic acid shows that the reactivity of carbonate is similar to that of the organic ligand oxalate. Because of pH effects on the speciation of these ligands in solution and on mineral surfaces, carbonate promoted weathering is especially important at near-neutral and basic pH. We propose that the generally termed ''carbonation weathering'', the effect of elevated subsurface PCO2 to accelerate rock weathering through suppression of pH, be extended to include the speciation and reactivity of inorganic carbon at neutral and near-basic pH.
Keywords: SILICATE; WEATHERING; FELDSPAR; CARBON DIOXIDE; CARBONATE; OXALATE